2018
DOI: 10.1111/joor.12710
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus as a comorbidity to temporomandibular disorders—A systematic review

Abstract: The aim of this systematic review was to evaluate the prevalence of tinnitus in patients with temporomandibular disorders (TMD) and the possible effects of TMD treatment on tinnitus symptoms. A search of the PubMed, Web of Science and Cochrane databases from inception of each database up to January 2017 found 222 articles. After independent screening of abstracts by two of the authors, we assessed 46 articles in full text. The inclusion and exclusion criteria reduced these to 25 articles of which 22 studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 44 publications
0
40
0
4
Order By: Relevance
“…Temporomandibular joint disorders (TMD) are quite common, with a prevalence between 10%−15% in the general population. 17 Women are affected twice as often as men and it is most common in the 20−40 age group. 17 A study of patients at a craniofacial pain clinic revealed 69% percent of TMD patients complained of aural symptoms, compared to 29% of patients without TMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporomandibular joint disorders (TMD) are quite common, with a prevalence between 10%−15% in the general population. 17 Women are affected twice as often as men and it is most common in the 20−40 age group. 17 A study of patients at a craniofacial pain clinic revealed 69% percent of TMD patients complained of aural symptoms, compared to 29% of patients without TMD.…”
Section: Discussionmentioning
confidence: 99%
“…17 Women are affected twice as often as men and it is most common in the 20−40 age group. 17 A study of patients at a craniofacial pain clinic revealed 69% percent of TMD patients complained of aural symptoms, compared to 29% of patients without TMD. 18 As other studies have reported, aural symptoms in TMD patients include otalgia, tinnitus, vertigo/dizziness, and subjective hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with findings described in previous studies, in which the larger portion of the sample was composed of women. 6,7,12,20,[22][23][24][25][26][27] To explain…”
Section: Discussionmentioning
confidence: 99%
“…4 Otological symptoms are frequent in individuals with TMD, and the most commonly cited in the literature are tinnitus (ringing in the ears), dizziness, vertigo, earache and a sensation of ear fullness. 1,[5][6][7] Some theories state that hyperactivity of the masticatory muscles generates problems in the stomatognathic system and, due to the anatomical proximity, the inner ears can be affected. 2,8 Parafunctional habits are defined as any nonfunctional neuromuscular activity of the stomatognathic system resulting from the repetition of an action that is considered pleasant by the individual exercising it.…”
Section: Introductionmentioning
confidence: 99%